Using farmer knowledge for participatory sweet-potato variety selection in Garut, West Java, Indonesia - Widyastuti, Caecilia Afra; Minantyorini (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper describes trials using sweet-potato germplasm from lrian Jaya, where sweet potatoes are a staple food in the highlands. During the collection of sweet-potato germplasm, farmers' knowledge of those sweet potatoes has also been collected. Fanners' knowledge about sweet potatoes in Irian Jaya will be used as a basis for this project and includes information on yields, the use of sweet potatoes as human food or reed for livestock, and the condition of Ihe environment.